Pusey and Transubstantiation: An Exploration of His Thinking and Ecumenical Implications. (14th December 2018) - Douglas, Brian
Abstract: This article seeks to explore the thinking of Edward Bouverie Pusey on the doctrine of transubstantiation. It begins by looking at the conflicted way Pusey is considered and goes on to examine Pusey's writings on transubstantiation. The article points out that Pusey's early writing on transubstantiation wrongly believed that the doctrine implied a carnal view of Christ's presence in the Eucharist, but that in his mature thinking this caricature was abandoned and he came to understand that transubstantiation is a form of moderate realism. Some detailed examination of Pusey's mature thinking is undertaken, including a very important set of correspondence between Edward Pusey and John Newman in 1867 which addressed the doctrine of transubstantiation. Pusey's thinking reveals that he is prepared to accept the word transubstantiation as long as it does not imply a change in the substance of the bread and wine of the Eucharist. The article concludes with discussion on the term transubstantiation itself and controversially cites evidence from both Anglican and Roman Catholic sources which suggest that the dependence on a particular scholastic philosophical analysis which attempts to explain the 'how' of the real presence of Christ in the Eucharist may be less useful than an approach of 'what'. Pusey's mature thinking on transubstantiation is seen as useful for ecumenical dialogue between the Anglican and Roman Catholic Churches.